Comparative Analysis Between the Empirical DNIT Method and the Mechanistic-Empirical MeDiNa in Flexible Pavement Design: A Case Study on BR-135 (Itacarambi–Manga Section) (International Journal of Geoscience, Engineering and Technology, 2025)
This study presents a comparative analysis between the empirical DNIT method and the mechanistic-empirical MeDiNa method for flexible pavement design. The research aimed to identify the conceptual and practical differences between the methodologies, highlighting calculation criteria, structural parameters, and long-term performance. Case studies and technical references were used to demonstrate the advantages of MeDiNa, such as greater accuracy in handling traffic, climate, and material variables, as well as the ability to estimate pavement behavior over time. On the other hand, the empirical DNIT method, although well-established, shows limitations under current conditions. The results indicate that MeDiNa represents a significant advancement, allowing for more efficient and durable designs, and is considered a superior alternative for modern pavement design in Brazil.